Racial Discrimination in the U.S. Labor Market: Employment and Wage Differentials by Skill - Daniel Borowczyk-Martins; Jake Bradley; Linas Tarasonis (Institute for the Study of Labor (IZA), 2014)
In the US labor market the average black worker is exposed to a lower employment rate and earns a lower wage compared to his white counterpart. Lang and Lehmann (2012) argue that these mean differences mask substantial heterogeneity along the distribution of workers' skill. In particular, they argue that black-white wage and employment gaps are smaller for high-skill workers. In this paper we show that a model of employer taste-based discrimination in a labor market characterized by search frictions and skill complementarities in production can replicate these regularities. We estimate the model with US data using methods of indirect inference. Our quantitative results portray the degree of employer prejudice in the US labor market as being strong and widespread, and provide evidence of an important skill gap between black and white workers. We use the model to undertake a structural decomposition and conclude that discrimination resulting from employer prejudice is quantitatively more important than skill differences to explain wage and employment gaps. In the final section of the paper we conduct a number of counterfactual experiments to assess the effectiveness of different policy approaches aimed at reducing racial differences in labor market outcomes.
Keywords: J31; J64; J71; 330; employment and wage differentials; discrimination; job search